McKenzie Cervical Exercise dan Stretching sebagai Upaya Penurunan Nyeri pada Neck Pain: Maulida Wijaya Putri, Muhammad Yusrin Al Gifari, Muslimah - Maulida Wijaya Putri; Muhammad Yusrin Al Gifari; Muslimah Muslimah (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2025)
Neck Pain is classified as one of the most common musculoskeletal disorders, typically arising from non-ergonomic working postures and repetitive static activities, particularly among professions such as teachers and office workers. This condition may increase pain intensity and interfere with daily functioning. Physiotherapy interventions, including McKenzie Exercise and stretching, are considered effective approaches to alleviate these symptoms. This study employed a one-group pretest–posttest design involving 27 teachers experiencing neck pain, who received physiotherapy interventions twice a week over a three-week period. The results of the Repeated Measures ANOVA with Huynh–Feldt correction revealed a p-value of 0.000 (p < 0.05), and the Pairwise Comparisons analysis with Bonferroni correction indicated significant differences in pain levels across all measurement intervals. These findings demonstrate that McKenzie Cervical Exercise and stretching are effective in reducing pain among individuals with Neck Pain.